161k views
4 votes
Use mathematical induction to prove the statement is true for all positive integers n, or show why it is false:

1^2+ 4^2+ 7^2 +...+(3n-2)^2 = n(6n^2-3n-1) / 2

1 Answer

5 votes

\text{Proof by induction:}

\text{Test that the statement holds or n = 1}


LHS = (3 - 2)^(2) = 1

RHS = (6 - 4)/(2) = (2)/(2) = 1 = LHS

\text{Thus, the statement holds for the base case.}


\text{Assume the statement holds for some arbitrary term, n= k}

1^(2) + 4^(2) + 7^(2) + ... + (3k - 2)^(2) = (k(6k^(2) - 3k - 1))/(2)


\text{Prove it is true for n = k + 1}

RTP: 1^(2) + 4^(2) + 7^(2) + ... + [3(k + 1) - 2]^(2) = ((k + 1)[6(k + 1)^(2) - 3(k + 1) - 1])/(2) = ((k + 1)[6k^(2) + 9k + 2])/(2)


LHS = \underbrace{1^(2) + 4^(2) + 7^(2) + ... + (3k - 2)^(2)}_{(k(6k^(2) - 3k - 1))/(2)} + [3(k + 1) - 2]^(2)

= (k(6k^(2) - 3k - 1))/(2) + [3(k + 1) - 2]^(2)

= (k(6k^(2) - 3k - 1) + 2[3(k + 1) - 2]^(2))/(2)

= (k(6k^(2) - 3k - 1) + 2(3k + 1)^(2))/(2)

= (k(6k^(2) - 3k - 1) + 18k^(2) + 12k + 2)/(2)

= (k(6k^(2) - 3k - 1 + 18k + 12) + 2)/(2)

= \frac{k(6k^(2) + 15k + 11) + 2}{}

= ((k + 1)[6k^(2) + 9k + 2])/(2)

= ((k + 1)[6(k + 1)^(2) - 3(k + 1) - 1])/(2)

= RHS

Since it is true for n = 1, n = k, and n = k + 1, by the principles of mathematical induction, it is true for all positive values of n.
User Hqjma
by
6.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.